The Impact of Ownership Structure on Corporate Social Responsibility - Waluyo, Waluyo (Opción, 2019)
The prime objective of the current study is to explore the link between ownership structure and corporate social responsibility by using the panel data methodology. Data of 5 years (2012-2016) is collected from the firm’s audited account. The findings of the study have shown a strong link between ownership structure and audit fee. In conclusion, the directors’ ownership structure of the organization may offer ascent to legitimacy gaps. Distinctive shareholders may request diverse disclosures and the interest is more significant to outsiders, due to the detachment between of administration and holders geographically, hold a high extent of shares.